Proceedings of the 7.1 International Conference in Digital Innovation - Sustainability Through the Lens of SDG (Selangor Malaysia University of Science and Technology, 2024)
The Conference focuses on the following areas: Environment, Social and Governance; Management, Marketing, Business, Finance and Economic; Sustainable Supply Chain Management & Logistics; Digital Technologies.